ANALISIS LITERATUR TENTANG MEDIA SOSIAL SEBAGAI ALAT DUKUNG KONSELING : TINJAUAN SYSTEMATIC LITERATURE REVIEW (SLR) TERHADAP PEMANFAATAN DIGITAL DALAM LAYANAN BIMBINGAN KONSELING DI SEKOLAH - Rizkika Romadhona; Busmayaril Busmayaril; Ali Murtadho (STKIP Pesisir Selatan, 2026)
This study aims to analyze the utilization of social media as a supporting tool in guidance and counseling services through a Systematic Literature Review (SLR) approach. The study uses data from 23 relevant scientific articles published between 2021 and 2026, sourced from Google Scholar and Scopus databases. The analysis process was carried out through stages of identification, selection, and data synthesis, supported by bibliometric analysis using VOSviewer to map research trends and topic relationships. The results show that social media plays a significant role in supporting guidance and counseling services, particularly in improving accessibility, flexibility, and students’ openness in counseling services, as well as encouraging the transformation of counseling services toward digital-based services. However, its implementation still faces challenges, including technological access gaps, limited counselor competence, and ethical and privacy issues. The novelty of this study lies in the SLR approach, which is able to synthesize comprehensive findings by integrating three main aspects: effectiveness, challenges, and strategies. These findings are expected to serve as a foundation for the development of more systematic and relevant digital-based guidance and counseling services.